We know that $$\sum_{n=0}^\infty C_nx^n=\frac{1-\sqrt{1-4x}}{2x}$$. But because $C_n=\frac1{n+1}\binom{2n}n=\frac{(2n)!}{n!(n+1)!}$, that sum is also $$\sum_{n=0}^\infty\frac{(2n)!}{(n+1)!}\frac{x^n}{n!}$$ $$=\sum_{n=0}^\infty\frac{(\frac12)_n(1)_n}{(2)_n}\frac{(4x)^n}{n!}$$ $$={}_2F_1(\frac12,1;2;4x)$$, so we get the identity $$_2F_1(\frac12,1;2;4x)=\frac{1-\sqrt{1-4x}}{2x}$$ My two questions are:
Is this correct?
Can you proof this identity without the use of generating functions or are there well-known hypergeometric series identities from which this follows?

  • $\begingroup$ Check out my edit to see how you can prevent the left-hand subscript on $_2F_1$ from being attached to the preceding symbol. $\endgroup$
    – joriki
    Jul 18, 2018 at 11:59
  • $\begingroup$ It's correct for $x=\dfrac14$ $\endgroup$
    – Nosrati
    Jul 18, 2018 at 12:04

1 Answer 1


This is correct: you can use one of the contiguous relations, in particular $$ (c-1)(F(c-)-F) = \frac{(c-b)F(b-)+(b-c+az)F}{1-z}, $$ which here becomes $$ F(1/2,1;1;4x)-F(1/2,1;2;4x) = \frac{F(1/2,0;2;4x)+(-1+2x)F(1/2,1;2;4x)}{1-4x}. $$ $F(a,0;c;z)=1$, and similarly it is easy to check that $F(a,b;b;z)=(1-z)^{-a}$, so we have $$ \frac{1}{\sqrt{1-4x}} = \frac{1}{1-4x} + \left( 1 + \frac{-1+2x}{1-4x} \right) F(1/2,1;2;4x) \\ \sqrt{1-4x} -1 = (-2x)F(1/2,1;2;4x), $$ and rearranging gives the result. The same strategy works for any hypergeometric functions with some parameters integers.


You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .